Calpain Inhibitor Calpeptin Alleviates Ischemia/Reperfusion-Induced Acute Kidney Injury via Suppressing AIM2 Inflammasome and Upregulating Klotho Protein - Wu, Yong; Yang, Huan; Cheng, Ming; Shi, Jialin; Zhang, Weichen; Liu, Shaojun; Zhang, Minmin (Frontiers in Medicine, 2022)
Renal ischemia/reperfusion injury is a major contributor of acute kidney injury (AKI), leading to renal cell necrosis, apoptosis, and inflammation. Calpains, a family of Ca2+-dependent cysteine proteases, play a pivotal role in the pathogenesis of renal diseases. Several studies have reported calpain inhibitors showing remarkable reno-protective effects against proteinuria and α-klotho deficiency-induced renal aging symptoms, particularly against glomerulus injury. However, little is known about the role of the calpain inhibitor calpeptin in acute kidney injury. The present study aims to investigate the potential mechanism of downregulation of Calpain 1 and 2 activity by calpeptin in the ischemia/reperfusion (IR)-induced AKI model. Firstly, we observed that the contents of Calpain 1 and 2 were significantly increased in the renal biopsy of clinical AKI patients, especially in the diseased tubules space. To investigate the impacts of calpain activity inhibition, we further pretreated with calpeptin in both the IR mouse model and in the HK-2 cells hypoxia model. We found that the calpain inhibitor calpeptin improved renal functional deterioration, attenuated pathological structure damage, and decreased tubular cell apoptosis in the IR injury-induced AKI mice model. Mechanistically, calpeptin significantly suppressed the AIM2 (absent in melanoma 2) and NLRP3 (NOD-like receptor protein 3) inflammasome signaling pathways and increased Klotho protein levels. Furthermore, immunofluorescence assays demonstrated that the application of calpeptin effectively inhibited Calpain 1 activation and gasdermin D (GSDMD) cleavage in the renal tubules of IR mice. Taken together, our both in vivo and in vitro experiments suggest that calpeptin conveyed reno-protection in AKI might be mediated by the inhibition of AIM2 inflammasome activation and upregulation of Klotho protein. As such, we provide new evidence that Calpain 1 and 2 activation may be closely associated with the pathogenesis of clinical AKI. The calpain-mediated AIM2 inflammasome signaling pathway and distinct interaction between calpain and Klotho may provide a potential novel preventative and therapeutic target for acute kidney injury.